Rough draft of history a century of US social movements in the news - Amenta, Edwin, 1957- (Princeton studies in American politics., 2022)
"The book offers a new view of U.S. social movement history across the twentieth century by examining how movement organizations were covered in major national newspapers. The book analyzes U.S. social movements--ranging from temperance to women's suffrage to the Tea Party and Occupy Wall Street--in a broad comparative fashion. Drawing on the full set of digitized newspapers from the twentieth-century (a task that as little as twenty years ago was considered impossible for researchers), the book offers both an institutional history of news--why the media covered what they covered, and to what effect--and also shows the influence of news coverage on a range of social mocements, from the well-known to the obscure. Media coverage is a crucial component of movement visibility; news can draw the general public into battles over new issues but also shapes how movements are perceived. The authors show how a movement's structure--it's organization, as well as the protest and non-protests activities it undertakes--influence its coverage, and consider too how macro political conditions shape movement coverage. They reveal surprising gaps between contemporaneous coverage and current scholarly focus; for instance, the labor movement received the most journalistic attention of any movement of the twentieth century, but it is greatly understudied in comparison to how much it dominated the public sphere. Taking stock of news coverage across a century of movements thus illuminates movements that were influential in public discourse but have been neglected by scholars. The authors end the manuscript by considering how recent developments--the rise of the internet and social media, the emergence of a powerful right-wing media system, and 24-hour news and the demise of many local newspapers and an overall decline in professional journalism--have aided right-wing movement actors in their bids for attention and for policy change at the expense of those on the left"--